Why information grows the evolution of order, from atoms to economies - Hidalgo, César A. 1979- (Basic Books, 2015)
Prologue; Introduction; PART I Bits in Atoms; 1 The Secret to Time Travel; 2 The Body of the Meaningless; 3 The Eternal Anomaly; PART II Crystallized Imagination; 4 Out of Our Heads!; 5 Amplifiers; PART III The Quantization of Knowhow; 6 This Time, It's Personal; 7 Links Are Not Free; 8 In Links We Trust; PART IV The Complexity of the Economy; 9 The Evolution of Economic Complexity; 10 The Sixth Substance; 11 The Marriage of Knowledge, Knowhow, and Information; PART V Epilogue; 12 The Evolution of Physical Order, from Atoms to Economies; Acknowledgments; Notes; Index